Professional practice levels and modalities, grounded in meaningful learning. Case: Management program UCLA (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2013)
This article is the result of an exploratory type research, which is analyzed as a preliminary the determining factors for the performance of a proposed internship at various levels and modalities, for curriculum Administration career Dean of Business Administration and Accounting from the University "Lisandro Alvarado". Methodologically, the work was conducted in three phases to diagnose the need for the inclusion of professional practice levels and types, then the determination of the key elements of the proposal based on the identification of competencies and finally show that the professional practices levels and types contribute to the development of employment skills. The population consisted of two thousand one hundred and fourteen subjects composed of forty teachers and two thousand and seventy-four students who have applied a previously validated instrument for expert opinion and reliability was determined through Cronbach's alpha method. For the determination of the key elements in identifying the skills, the population was fourteen teachers who have applied an instrument, in order to meet the management of the contents of the syllabi. The results of the diagnosis showed the need to incorporate professional practice levels and types as well as the contents of the syllabi of specific axis management career and develop generic and specific skills gradually and systematically. Conclusions and recommendations are proposed for the design of the proposal applied to professional practices to be carried out consecutively in semesters: V, VII and X. under a methodology based on meaningful learning.
Keywords: competencies; levels and modalities in professional practice